2023
DOI: 10.1177/26323524231198542
|View full text |Cite
|
Sign up to set email alerts
|

Perceived policy-related barriers to palliative care implementation: a qualitative descriptive study

Atsede Aregay,
Margaret O’Connor,
Jill Stow
et al.

Abstract: Background: Ethiopia has a national palliative care guideline, and palliative care is explicitly recognised in the country’s healthcare policy and health sector transformation plans. However, palliative care is not fully delivered in the regional public hospitals and primary health care units. Objective: This study explores perceived policy barriers to deliver palliative care services in rural and regional healthcare settings, which primary healthcare units largely serve. Design: Face-to-face interviews were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Ethiopia follows a three-tier health care system: namely, primary health care units (PHCU), secondary care (general hospital) and tertiary care (comprehensive specialized hospital) [ 14 ]. The study setting details are reported fully elsewhere [ 28 – 30 ]. The national palliative care guideline described in detail where and how palliative care should be be integrated in each of these levels of health care system [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ethiopia follows a three-tier health care system: namely, primary health care units (PHCU), secondary care (general hospital) and tertiary care (comprehensive specialized hospital) [ 14 ]. The study setting details are reported fully elsewhere [ 28 – 30 ]. The national palliative care guideline described in detail where and how palliative care should be be integrated in each of these levels of health care system [ 31 ].…”
Section: Methodsmentioning
confidence: 99%